Tutorat de langue par visioconférence : comment former aux régulations pédagogiques ? - Nicolas Guichon; Samira Drissi (Recherches en didactique des langues et des cultures)
The aim of this article is to contribute insight on how to train language instructors for online teaching. The context of this study is a programme in which French as a foreign language trainee instructors tutor American learners of French at a distance via a desktop videoconferencing platform. Trainees engage in this novel professional activity with what pedagogical and communicational resources they have and manage the eight weekly sessions of synchronous language lessons as best they can. They regulate these sessions with utterances and actions aimed at guiding learners' activities. These instructional regulations, which were collected using screen capture software, provide access to emerging pedagogical and communicational strategies. The work conducted on this multimodal corpus offers insights into some aspects of synchronous online pedagogy. It results in the proposal of criteria for evaluation of instructional regulations in order to improve the training of online language tutors.